History of madness - Foucault, Michel (Routledge, 2006)
When it was first published in France in 1961 as Folie et Deraison: Histoire de la Folie a l'age Classique, few had heard of a thirty-four year old philosopher by the name of Michel Foucault. By the time an abridged English edition was published in 1967 as Madness and Civilization, Michel Foucault had shaken the intellectual world.